Presidential Policies’ Effects on Oil and Gas Price and Productions Within the United States from 1977-2021 - Nie, Dongfang; Engels, Lacia; Zhang, Jingbo (Journal of Applied Business and Economics, 2022)
Amidst the ongoing COVID-19 pandemic, the contentious U.S. 2020 presidential election featured candidates with quite different stances on regulating the oil and gas industry, leaving many to question the longevity of fossil fuel use. However, little research explores the relationship between presidential policies and the oil market. In this paper, extensive research into presidential energy policies and their effects on domestic oil prices and production dating back to 1977 helps us identify whether we can predict the industry’s future under Joe Biden’s administration. The paper’s results suggest the domestic oil industry is more dependent on external foreign events – with presidential policies offering almost negligible effects on prices and production.